Measuring the research productivity on environmental toxicology: A scientometric study - Shanmuganathi Ayyankalai; Srinivasaragavan Subburaj; Prasanna Kumari Nataraj (The Scientific Temper, 2025)
This paper attempts to highlight the growth and development of Environmental Toxicology literature and to make the quantitative and qualitative assessment by way of analyzing various facets of research output and Citations impact based on the Web of Science database. A total of 6,663 publications were published on Environmental Toxicology, which received 183279 Citations in 2022. There were 126 countries involved in the Environmental Toxicology research. The most productive countries are the USA, having the highest share of 3,051 publications and receiving 105322 Citations, followed by the People’s Republic of China with 653 Citations with 13660 publications, Germany with 594 Citations for 21,315 publications, Canada with 575 Citations for 19,869 publications, England with 568 Citations for 24408 publications and so on. The most productive Institutions were the United States Environmental Protection Agency (USEPA) with 459 publications (17879 Citations), followed by USEPA with 65 publications (3822 Citations), and NIH National Institute of Environmental Health Sciences NIEHS 54 publications (3257citations); it noted that 6 Institutes were registered more than 20 Publications and 25 Institutions were recorded more than 1000 Citations. The highly Cited journals are Environmental Toxicology and Chemistry with 10425 Citations for 577 Publications, Integrated Environmental Assessment and Management (IEAM) with 1436 Citations for 220 publications; Environmental Health Perspectives, with 1476 Citations for 162 publications; Environmental Health Perspectives, with 5332 Citations for 195 publications, and Toxicological Sciences with 729 Citations for 187 publications. The study found that 10 source titles were registered in more than 600 Citations, and most of the publications are published in high-impact journals. This paper also reveals the collaborating institutions, countries, authorship and publication pattern. In the journal, Current Computer-aided Drug Design entitled “Quantitative Structure-activity Relationships of Aquatic Narcosis,” Adhikari and Mishra explores the quantitative structure-activity relationships (QSAR) of aquatic narcosis and offer a comprehensive review of the field. Also, this article has a Local Citation Score of 2, a Global Citation Score of 11, a Local Citation Rank of 3. It has been cited 191 times, highlighting its influence and relevance in the area of drug design and environmental toxicology. Also, in another journal, the International Journal of Environmental Health Research, entitled “Cellular Mechanisms of Cadmium-Induced Toxicity: A Review,” Rani et al. explain the cellular mechanisms involved in cadmium-induced toxicity by providing an in-depth analysis of how cadmium affects biological systems Further this article has a local citation score (LCS) of 2, a Global Citation Score of 11, LCS of 3, and has been cited 191 times, highlighting its influence and relevance in the area of drug design and environmental toxicology. Hence, it is identified that India ranks 17th position and has 157 publications in environmental toxicology that are covered by internationally reputed indexing sources